YOUTH SLANG IN THE SPEECH OF MODERN STUDENTS - Hanova Dilrabo Baratovna (Galaxy International Interdisciplinary Research Journal, 2021)
The relevance of the work is due to the need to study the lexical space of the modern Russian language, to describe the trends that form the speech portrait of modern youth. The semantics and etymology of slang vocabulary is analyzed on the basis of the results of a survey, the respondents of which were first-year students of the University. The purpose of the article is, on the basis of students' vocabulary, to consider the main mechanisms of the functioning of youth slang, to identify the sources of its replenishment, to determine the meanings of the most frequent jargon, to identify the reasons for the use of this lexical layer by university students. Research materials can be useful for linguists, sociologists, copywriters, psychologists and other professionals.